Integrative Single-Cell RNA-Seq and ATAC-Seq Analysis of Mesenchymal Stem/Stromal Cells Derived from Human Placenta - Li, Jinlu; Wang, Quanlei; An, Yanru; Chen, Xiaoyan; Xing, Yanan; Deng, Qiuting; Li, Zelong; Wang, Shengpeng; Dai, Xi; Liang, Ning; Hou, Yong; Yang, Huanming; et al. (Frontiers in Cell and Developmental Biology, 2022)
Mesenchymal stem/stromal cells derived from placenta (PMSCs) are an attractive source for regenerative medicine because of their multidifferentiation potential and immunomodulatory capabilities. However, the cellular and molecular heterogeneity of PMSCs has not been fully characterized. Here, we applied single-cell RNA sequencing (scRNA-seq) and assay for transposase-accessible chromatin sequencing (scATAC-seq) techniques to cultured PMSCs from human full-term placenta. Based on the inferred characteristics of cell clusters, we identify several distinct subsets of PMSCs with specific characteristics, including immunomodulatory-potential and highly proliferative cell states. Furthermore, integrative analysis of gene expression and chromatin accessibility showed a clearer chromatin accessibility signature than those at the transcriptional level on immunomodulatory-related genes. Cell cycle gene-related heterogeneity can be more easily distinguished at the transcriptional than the chromatin accessibility level in PMSCs. We further reveal putative subset-specific cis-regulatory elements regulating the expression of immunomodulatory- and proliferation-related genes in the immunomodulatory-potential and proliferative subpopulations, respectively. Moreover, we infer a novel transcription factor PRDM1, which might play a crucial role in maintaining immunomodulatory capability by activating PRDM1-regulon loop. Collectively, our study first provides a comprehensive and integrative view of the transcriptomic and epigenomic features of PMSCs, which paves the way for a deeper understanding of cellular heterogeneity and offers fundamental biological insight of PMSC subset-based cell therapy.